Energy–water nexus under energy mix scenarios using input–output and ecological network analyses. (1st January 2019) - Wang, Saige; Fath, Brian; Chen, Bin
Highlights: Input–output and ecological network analyses were combined with future energy generation mix scenarios. Nexus impact on the water system was larger than that on the energy system. Tradeoffs between energy, water and carbon for different energy generation mix scenarios were analyzed. Abstract: Increasing demand for energy, an evolving electricity-generation mix, and water demand from competing sectors have important implications for water budgets and energy planning. To evaluate the water-related impacts of energy-related decisions, we built a national energy–water nexus scenario analysis assessment framework by extending input–output analysis (IOA) to future energy mix scenarios of China. The scenarios for China out to 2050 include four low-carbon-development scenarios that are planned in climate change mitigation roadmaps and one baseline scenario. Sectoral direct energy, direct water, water-related energy, and energy-related water consumption were inventoried. Sectoral embodied consumption of water and energy and their inter-sector flows were mapped using IOA to create energy–water nexus networks. A sectoral nexus was defined to investigate the impact of the energy–water linkage on energy and water systems. Sectoral control and dependence relationships were revealed by ecological network analysis. Results showed that nexus impact on the water system was larger than that on the energy system. The main export and import pairs—Chemical industry–Agriculture (Ag), Manufacturing–Ag, Ag–Metal smelting and pressing (Me), and Me–Electricity (El)—should be critical pathways for nexus management via the adjustment of sectoral economic relationships. The sectors with a high nexus impact—Ag, El, and Me—should decrease their energy and water consumption to achieve outsized system-wide savings. Sectors with a low nexus impact—such as domestic services; transport, storage and post services; and water production and supply—can increase their energy and water consumption with a lesser impact on the wider system. The low-carbon-development scenario exhibited the lowest nexus impact, followed by the enhanced low-carbon scenario, whose energy mix also exerted the lowest pressure on the water system. By analyzing the tradeoffs between energy, water, and carbon emissions under five scenarios, this study provides insights for nexus management on how to balance water shortage issues and the development of energy generation in future energy and water resource planning.